Understanding and addressing the challenges of learning computer-mediated Dynamic Assessment: A teacher education study. (May 2018) - McNeil, Levi
Although the second language literature on Dynamic Assessment (DA) – the unity of assessment and instruction into a singular activity to promote cognitive development – shows promising results, very little has been written about how to educate teachers to use it. This two-cycle, exploratory action research study aimed to understand and address the challenges that the pre- and in-service teachers faced while participating in a graduate course introducing computer-mediated DA. Data from reflective journals, surveys, and transcripts from synchronous online DA tutoring sessions showed that the teachers in Cycle 1 experienced problems managing the levels of the mediating strategies that they used, which was related to the issues of utilizing course-embedded supports, dealing with task pressures, and understanding the DA concept. After modifying the course to attend to these issues, the study found that the Cycle 2 teachers exhibited greater control over the mediating strategies they employed during tutoring sessions than the teachers in Cycle 1. This study presents a contextualized account of certain issues that may arise when introducing DA and ways to manage them. More broadly, the findings underscore the importance of teacher educators investigating their own practices, and highlight the need to connect the concepts that teachers are studying with meaningful and well-supported opportunities for use.